2013
DOI: 10.5352/jls.2013.23.12.1516
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanogenesis in B16F0 Melanoma Cells by Extract of Fermented Cordyceps militaris Containing High Cordycepin

Abstract: To find a novel skin whitening agent, the effect of cordycepin-enriched Cordyceps militaris (CMα) extract fermented by fungi on anti-melanogenesis in B16F0 mouse melanoma cells was investigated.Fermented CMα was prepared with fungi, including Monascus purpureus (Mp), Aspergillus oryzae (Ao), Aspergillus kawachii (Ak), and Rhizopus oryzae (Ro), respectively. When the content of the phenolics and the flavonoids and the activities of the antioxidant and the mushroom tyrosinase inhibition were measured in the CM f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As studied previously, tyrosinase inhibition was initially focused on cordycepin extract prepared from the fruiting bodies of C. militaris. Cha and Kim demonstrated that cordycepin can suppress cellular tyrosinase activity and melanin production in cultured B16F0 melanoma cells [61]. Subsequently, Li et al [62] reported that both cordycepin and the mycelia of C. militaris extracted using boiling water can provide tyrosinase-inhibition activity.…”
Section: Tyrosinase Inhibitory Activity Of Crude Sbr Extractsmentioning
confidence: 99%
“…As studied previously, tyrosinase inhibition was initially focused on cordycepin extract prepared from the fruiting bodies of C. militaris. Cha and Kim demonstrated that cordycepin can suppress cellular tyrosinase activity and melanin production in cultured B16F0 melanoma cells [61]. Subsequently, Li et al [62] reported that both cordycepin and the mycelia of C. militaris extracted using boiling water can provide tyrosinase-inhibition activity.…”
Section: Tyrosinase Inhibitory Activity Of Crude Sbr Extractsmentioning
confidence: 99%
“…The results suggested that the inhibition of melanin synthesis in B16-F10 melanoma cells by ME was significantly higher than that of arbutin, while the inhibition of melanin production by HE was significantly lower than that of arbutin. Cha and Kim [51] demonstrated that fermented extract of Cordyceps militaris exhibited 66-47% melanin synthetic activity at 1.0-3.0 mg/mL in B16-F10 melanoma cells, suggesting that inhibitory activity of melanin synthesis of fruiting body extracts of Ph. vaninii were higher than that of fermented extract of Cordyceps militaris.…”
Section: Melanin Synthesis Activitymentioning
confidence: 99%
“…C90 and C98 at a test duration of 72 hours showed better results in reducing the melanin content the water extract of Cordyceps militaris, where at a concentration of 5 mg/ml for 72 hours the melanin content was 59.8% in B16F0 cells (Cha and Kim, 2013). This result is different when compared with EGCG from tea extract, where at a concentration of 12.5 µg/ ml for 72 hours the melanin content in cells ranges from 20% to 52% in Melan-A cells (Kim et al, 2015), compared to C90 O n l i n e F i r s t and C98 where at a concentration of 10 µg/ml for 72 hours the melanin content was 76.7% and 62.1% in B16F0 cells, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…The results of this study are expected to provide information about the potential of gambir catechins as depigmenting agents. In this study, 3-isobutyl-1-methylxanthine (IBMX) was used to stimulate the process of melanogenesis in B16F0 cells (Cha and Kim, 2013). This study provides an additional list of compounds that can be formulated in cosmetic preparations as lightening agents.…”
Section: Introductionmentioning
confidence: 99%